BUERGER’S DISEASE IN PATIENT WITH DIABETES MELLITUS - CASE STUDY - Dr. Sunil Kumar N; Dr. Sunil Ramachandra Khandare (The Bioscan, 2025)
Buerger's disease [Thromboangiitis Obliterans] is a non-atherosclerotic inflammatory disease of unknown etiology, which has a strong association with tobacco. We present here one case of Buerger’s disease associated with type II Diabetes Mellitus successfully treated with the help of ayurveda management.